KARAKTERISASI KOKRISTAL PARASETAMOL – ASAM SUKSINAT MELALUI METODE SOLVENT DROP GRINDING - Haeria Haeria; Asia Musfikah; Muh Fitrah (Universitas Islam Negeri Alauddin Makassar, 2014)
paracetamol - succinic acid. This study aims to determine whether the formation of paracetamol kokrital using succinic acid using solvent-drop grinding method is based on the analysis of the characterization of the structure and determine the dissolution rate of paracetamol kokristal - suksint acid produced.The formation of paracetamol kokristal-succinic acid (1: 1) using the method of solvent drop grinding with the addition of ethanol. Characterization of the structure using Faurier Transform Infra-Red (FT-IR), Differential Scanning Calorimetry (DSC) and X-Ray difractometry (XRD), and surface morphology observation and observation by microscope Scanning Electron Microscope (SEM), as well as the dissolution test methods basketball the dissolution medium artificial gastric fluid without pepsin pH 1.2.The results showed that cocristalisasi parasetamol-cocristal succinic acid forming phase. Decreasein the instrument DSC melting point of 580C becomes 156.170C185 temperature, the XRD instrumentwithinterferencethere is a new peak at 2θ peak 20, 3000; 25, 15,000; 35, 10,000. FT-IR instrumentsareshiftingwave number 3163.26cm-1 and 3111.16cm-1 to 3159.40 cm-1 and 3109.25cm-1.